2001
DOI: 10.1021/ma001727a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polystyrene-b-polyisoprene Diblock Copolymers by Liquid Chromatography at the Chromatographic Critical Condition

Abstract: In the chromatographic separation of macromolecules with a porous stationary phase, the retention is determined by both size exclusion and interaction mechanisms. At the chromatographic critical condition, the effects due to the two separation mechanisms compensate each other, and the retention of homopolymer molecules becomes independent of molecular weight. Liquid chromatography at the critical condition has attracted much interest for the characterization of block copolymers since it might permit the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 33 publications
12
112
1
Order By: Relevance
“…These simulation results confirmed the previous experimental observations [108,109]. Moreover, Wang's group also studied the retention behavior of star-shaped PS in LCCC of linear PS.…”
Section: Predicting Chromatographic Separation For Polyolefins Based supporting
confidence: 87%
“…These simulation results confirmed the previous experimental observations [108,109]. Moreover, Wang's group also studied the retention behavior of star-shaped PS in LCCC of linear PS.…”
Section: Predicting Chromatographic Separation For Polyolefins Based supporting
confidence: 87%
“…Recently, Chang et al reported that the polyA block in a diblock or triblock linear copolymer was not completely ''invisible'' at the LCCC analysis, and the elution behavior of the block copolymer was affected to some extent by the length and architecture of the ''invisible'' block. [34,35] These results were different from the theoretical assumption and the experimental results of Falkenhagen et al, who analyzed the diblock copolymer, poly(methyl methacrylate)-poly(tert-butyl methacrylate) (polyMMApolytBMA), under the LCCC for polyMMA and polytBMA separately and proved that the ''invisible'' block had no influence on the elution behavior of block copolymers. [43] In order to evaluate the ''invisibility'' of polyMA block during the LCCC analysis of polyMA-containing block copolymer, series of polySt-polyMA linear and 3-arm star copolymers were synthesized.…”
Section: Evaluation Of Lccc Accuracymentioning
confidence: 63%
“…An interesting application of LCCC is the characterization of block copolymers [32][33][34][35][36] since it is important to evaluate the efficiency of initiation from the MI during the synthesis of block copolymers. A theoretical model shows that under the critical condition for polyA homopolymer, the elution behavior of polyA-polyB block copolymer (polyA is defined as MI) is entirely dependent on the length of polyB block; while under the critical condition for polyB homopolymer, the elution behavior of the block copolymer depends only on the length of polyA block.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Chang used LC-CC, solvent gradient HPLC and temperature gradient interaction chromatography (TGIC) for the separation with regard to chemical composition. [12,[34][35][36][37] In the present study, special attention is given to the proper analysis of the molar masses and polydispersities of the precursor blocks, the block copolymers, and the single blocks of the block copolymers. It is known, that living anionic polymerization produces polymers with narrow polydispersities, usually much less than 1.1 (M w =M n ).…”
Section: Introductionmentioning
confidence: 99%